Chronic Candida albicans Meningitis in a 4-Year-Old Girl with a Homozygous Mutation in the CARD9 Gene (Q295X). Issue 9 (September 2015) - Herbst, Martin; Gazendam, Roel; Reimnitz, Denise; Sawalle-Belohradsky, Julie; Groll, Andreas; Schlegel, Paul-Gerhardt; Belohradsky, Bernd; Renner, Ellen; Klepper, Jörg; Grimbacher, Bodo; Kuijpers, Taco; Liese, Johannes
Abstract : A 4-year-old Turkish girl of consanguineous parents was hospitalized for the evaluation of headaches and recurrent febrile episodes of unknown origin. Her medical history was unremarkable except for a few episodes of uncomplicated oral thrush. Meningitis was diagnosed, and Candida albicans was the only pathogen identified by polymerase chain reaction and culture. Despite systemic antifungal multidrug therapy, a prolonged course of 16 months of therapy was necessary to clear C. albicans from the cerebrospinal fluid. Molecular genetic analysis revealed a homozygous caspase recruitment domain 9 ( CARD9 ) mutation (Q295X), which was reported to predispose to chronic mucocutaneous candidiasis. Immunologic workup excluded predisposing B-cell and T-cell defects. In addition, T cells producing interleukin-17 were repeatedly measured within the normal range. Analyses of neutrophils demonstrated normal nicotinamide adenine dinucleotide phosphate oxidase activity in response to various stimuli including Staphylococcus aureus and C. albicans . Additional neutrophilic functional testing, however, showed a decreased cytotoxicity to nonopsonized C. albicans, indicating an impaired killing mechanism against Candida spp. independent from the production of reactive oxygen species by the nicotinamide adenine dinucleotide phosphate oxidase system. Because this defect was only demonstrated in the absence of opsonins, it might especially predispose to chronic C. albicans infections in the central nervous system where opsonin concentrations are usually low. We, therefore, suggest that due to an additional neutrophil dependent defect CARD9 deficiency predisposes not only to chronic mucocutaneous candidiasis, but also to invasive chronic Candida infections, especially of the central nervous system. Abstract : Supplemental Digital Content is available in the text.